Combinatorial Library of Improved Peptide Aptamers, CLIPs to Inhibit RAGE Signal Transduction in Mammalian Cells - Reverdatto, Sergey; Rai, Vivek; Xue, Jing; Burz, David S.; Schmidt, Ann Marie; Shekhtman, Alexander (PLOS ONE, 2013)
Peptide aptamers are small proteins containing a randomized peptide sequence embedded into a stable protein scaffold, such as Thioredoxin. We developed a robust method for building a Combinatorial Library of Improved Peptide aptamers (CLIPs) of high complexity, containing ≥3×1010 independent clones, to be used as a molecular tool in the study of biological pathways. The Thioredoxin scaffold was modified to increase solubility and eliminate aggregation of the peptide aptamers. The CLIPs was used in a yeast two-hybrid screen to identify peptide aptamers that bind to various domains of the Receptor for Advanced Glycation End products (RAGE). NMR spectroscopy was used to identify interaction surfaces between the peptide aptamers and RAGE domains. Cellular functional assays revealed that in addition to directly interfering with known binding sites, peptide aptamer binding distal to ligand sites also inhibits RAGE ligand-induced signal transduction. This finding underscores the potential of using CLIPs to select allosteric inhibitors of biological targets.